Sovereign risk and bank lending: Theory and evidence from a natural disaster - Yusuf Soner Başkaya; Bryan Hardy; Şebnem Kalemli-Ozcan; Vivian Z. Yue (Federal Reserve Bank of Atlanta, 2023)
We quantify the sovereign-bank doom loop by using the 1999 Marmara earthquake as an exogenous shock leading to an increase in Turkey's default risk. Our theoretical model illustrates that for banks with higher exposure to government securities, a higher sovereign default risk implies lower net worth and tightening financial constraint. Our empirical estimates confirm the model's predictions, showing that the exogenous change in sovereign default risk tightens banks' financial constraints significantly for banks that hold a higher amount of government securities. The resulting tighter bank financial constraints translate into lower credit provision, suggesting that there is a significant balance-sheet channel in transmitting a higher sovereign default risk toward real economic activity.
Keywords: E32; F15; F36; O16; 330; banking crisis; bank balance sheets; lending channel; public debt; credit supply